From skillful to empathic: evaluating shifts in medical students' perceptions of surgeons through a combined patient as teacher and arts-based reflection program - Gurjot K Gill; Stella L Ng; Emilia Kangasjarvi; Jeff Crukley; Jory S Simpson (Canadian Medical Education Journal, 2023)
Introduction: The purpose of this study was to identify whether the incorporation of a combined Patient as teacher (PAT) and arts-based reflection (ABR) program during a surgical clerkship rotation could influence more humanistic perceptions of surgeons, using an innovative evaluation approach.